Towards Intensifying Media Efforts as a Strategy to Raise Environmental Awareness - Saghour, Hichem (جامعة محمد خيضر بسكرة - كلية الحقوق والعلوم السياسية, 2024)
إن التغيرات المناخية التي يشهدها العالم قد زادت من وعي المجتمع الدولي على إيجاد سبل جديدة للحفاظ على البيئة موازية للترتيبات الدولية التي وضعت من أجل الحفاظ على البيئة من خلال التجمعات والمؤتمرات الدولية، وعليه فإن هذا المقال يركز على دور الإعلام البيئي وانعكاساته على المحيط البيئي، حيث يبين دور مختلف وسائل الإعلام في نشر الوعي البيئي بين أفراد المجتمع ومدى انعكاساته على المدى البعيد والقصير. The climate changes the world is witnessing have increased the international community's awareness of finding new ways to preserve the environment, parallel to the international arrangements that have been made to preserve the environment through international gatherings and conferences. Accordingly, this article focuses on the role of environmental media and its repercussions on the environment. It shows the role of various media in spreading environmental awareness among members of society and the extent of its repercussions in the long and short term.
Keywords: الوعي البيئي -- التغييرات المناخية -- وسائل الإعلام -- المؤتمرات الدولية